The effect of controlled degradation with an organic peroxide on the molecular characteristics and properties of heterophasic propylene-ethylene copolymers (HECO) - Swart, Morne (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.